The Role of Material Flow Cost Accounting In Production Efficiency And Waste Reduction In Karya 27 Perabot - Alyani Rahma Putri; Muthi Maitsa Zulfatri (Journal of Engineering Science and Technology Management, 2025)
This study aims to analyze the efficiency of the production process in micro, small, and medium enterprises (MSMEs) producing wooden furniture, with a case study of Karya 27 Perabot, which has been operating since 2019. To achieve this objective, this study adopted the Material Flow Cost Accounting (MFCA) approach, an environmental accounting method that allows for the measurement and assessment of costs associated with wasted materials and energy in the production flow. The main focus of this study is to identify and quantify losses in the form of wood, paint, and energy waste, as well as to analyze the potential for implementing Green Productivity (GP) to improve the efficiency and sustainability of the company's operations. The results show that 22.5% of total production costs consist of losses, with wood as the largest contributor (77.8%). Furthermore, the implementation of the Green Productivity (GP) strategy is predicted to significantly reduce losses, with potential cost savings reaching IDR 325,000 per batch, or approximately IDR 3.9 million per year. This study provides empirical insights into the application of MFCA in the context of furniture MSMEs and suggests strategic steps that can improve operational efficiency while supporting environmental sustainability goals in the small manufacturing industry sector.